The relationship of localized rainfall versus urban heat island (UHI) parameters and air pollution - Ahmad, Mohd Nazmi; Mohd Sidek, Lariyah; Selamat, A.; Zainal Abidin, Roseli (2012)
As Malaysia advancing to a developed nation in 2020 and beyond, more people would live in urban than in the rural areas. In recent years, localized rainfall; high air pollution, temperature, and humidity; and uneven rain distribution occur in Malaysia. Higher population needs higher clean water consumption. Globally, the Urban Heat Island (UHI) and air pollution and associated environmental parameters are generally correlated to urban size and its population. Lack of proper industrial urban planning, the UHI would certainly significant in Malaysia. It is hypothesized that UHI is positively related to the localized rainfall that causing flesh flood and possibly yielding ‘acidic’ rainfall and it is presumably to occur in the urban industrial areas. Due to the phenomena in forecast, the descriptive, comparative, and mathematical modeling studies in identifying the occurrence of localized rainfall and UHI, and their relationship with selected meteorological and air pollutant parameters of selected Malaysian cities associated Petaling Jaya/Subang industrial area and residential of Shah Alam based on selected green areas were carried out. The study had revealed that the occurrence of localized rainfall could be identified for urban industrial area that experiencing higher air pollutant levels (especially CO, NO2, and SO2) with slower wind speed (as compared to residential area of Shah Alam) and probably with higher air temperature. Presumably, above had indicated that the localized rainfall was then related to UHI in the area. The non-linear mathematical model was successfully developed and validated in predicting the rainfall (normal plus localized rain) based on the selected parameters humidity, wind direction and speed, air temperature, and air pollutants for the study industrial area. The above preliminary results suggested that similar studies should be conducted for other Malaysia industrial cities since the developed model (site-specific) could be used for the proper industrial urban planning and development in reducing the impact of UHI. This could be related in assisting the planning of activities and actions in purifying the yielded rain water as part of river rehabilitation (rainfall harvesting treatment technology) and to propose the green technology (green roof) to reduce the impact of urban heat island (UHI) in industrial urban as compared with that of the rural or area with full vegetation cover.